Microstereolithography and characterization of poly(propylene fumarate)-based drug-loaded microneedle arrays. (30th September 2015) - Lu, Yanfeng; Mantha, Satya Nymisha; Crowder, Douglas C; Chinchilla, Sofia; Shah, Kush N; Yun, Yang H; Wicker, Ryan B; Choi, Jae-Won
Abstract: Drug-loaded microneedle arrays for transdermal delivery of a chemotherapeutic drug were fabricated using multi-material microstereolithography ( μ SL). These arrays consisted of twenty-five poly(propylene fumarate) (PPF) microneedles, which were precisely orientated on the same polymeric substrate. To control the viscosity and improve the mechanical properties of the PPF, diethyl fumarate (DEF) was mixed with the polymer. Dacarbazine, which is widely used for skin cancer, was uniformly blended into the PPF/DEF solution prior to crosslinking. Each microneedle has a cylindrical base with a height of 700 μ m and a conical tip with a height of 300 μ m. Compression test results and characterization of the elastic moduli of the PPF/DEF (50:50) and PPF/drug mixtures indicated that the failure force was much larger than the theoretical skin insertion force. The release kinetics showed that dacarbazine can be released at a controlled rate for five weeks. The results demonstrated that the PPF-based drug-loaded microneedles are a potential method to treat skin carcinomas. In addition, μ SL is an attractive manufacturing technique for biomedical applications, especially for micron-scale manufacturing.